Studi Pendahuluan Adanya Senyawa Flavanoid Pada Tumbuhan Sarang Semut (Myrmecodia tuberosa) - Sudding, .; Alimin, .; Muhaedah, . (bionature, 2010)
This study aimed to isolation and characterization the flavonoid compounds in plants ant nest (M. tuberose) from Village District Majannang Parigi, Gowa regency in South Sulawesi. This research was conducted through several phases, namely: sample preparation, isolation and characterization. Isolation starting from extraction, followed by fractionation and purification, among others, by recrystallization, then performed characterization, which among others, performed with test reagent 1% AlCl3 in ethanol, FeCl3 and with benedict, thin layer chromatography and melting point test. Results of research conducted on the basis of several characterization, obtained pure compounds form crystals amount of 220 mg of yellowish white, needle-shaped, with melting point 116-117 Âº C, Rf with eluen BAA by 71, reacted positively to the reagent 1% AlCl3 in ethanol which is marked yellow spots occur and with reagent benedict give a light blue under UV light, reasonably suspected that the compound obtained is a type of flavone of flavonoid compounds.